Dieulafoy lesion in duodenum of child successfully treated by transcatheter embolization: A case report - Ming-Yi Shang; Ling Peng; Jun Ma (Elsevier, 2015)
A 15-year-old boy had massive bleeding from Dieulafoy lesion of the duodenum. An emergency GI endoscopy revealed clot in duodenum while angiography showed extravasation of contrast medium from the right gastric artery. Transcatheter superselective embolization was performed and stopped the bleeding completely.